Covalency, correlations, and interlayer interactions governing the magnetic and electronic structure of Mn3Si2Te6 - Bigi, C; Qiao, L; Liu, C; Barone, P; Hatnean, MC; Siemann, G-R; Achinuq, B; Mayoh, DA; Vinai, G; Polewczyk, V; Dagur, D; Mazzola, F; et al. (American Physical Society, 2023)
Mn3Si2Te6 is a rare example of a layered ferrimagnet. It has recently been shown to host a colossal angular magnetoresistance as the spin orientation is rotated from the in- to out-of-plane direction, proposed to be underpinned by a topological nodal-line degeneracy in its electronic structure. Nonetheless, the origins of its ferrimagnetic structure remain controversial, while its experimental electronic structure, and the role of correlations in shaping this, are little explored to date. Here, we combine x-ray and photoemission-based spectroscopies with first-principles calculations to probe the elemental-selective electronic structure and magnetic order in Mn3Si2Te6. Through these, we identify a marked Mn-Te hybridization, which weakens the electronic correlations and enhances the magnetic anisotropy. We demonstrate how this strengthens the magnetic frustration in Mn3Si2Te6, which is key to stabilizing its ferrimagnetic order, and find a crucial role of both exchange interactions extending beyond nearest-neighbors and antisymmetric exchange in dictating its ordering temperature. Together, our results demonstrate a powerful methodology of using experimental electronic structure probes to constrain the parameter space for first-principles calculations of magnetic materials, and through this approach, reveal a pivotal role played by covalency in stabilizing the ferrimagnetic order in Mn3Si2Te6.